Azospirillum improves lettuce growth and transplant under saline conditions - Fasciglione, Gabriela (2012)
BACKGROUND: Recent studies have shown that as a plant-growth-promoting rhizobacteria (PGPR), Azospirillum inoculation could contribute to the mitigation of the negative effects caused by salt on lettuce growth. Moreover, the use of PGPR to alleviate the effects of transplant in vegetables has also been recognized. However, the scarce data available on the use of Azospirillum to improve lettuce growth before and after transplant under saline conditions prompted us to focus our research on this topic. RESULTS: Early germination and seedling settlement of seeds exposed to 0 and 40 mol m−3 NaCl were clearly improved by Azospirillum inoculation. At 0 mol m−3 NaCl, plant establishment, leaf mass and root mass parameters before transplant were significantly higher in inoculated plants than in non-inoculated controls. At harvest, leaf fresh weight, ascorbic acid content and plant survival to transplant were also significantly higher in Azospirillum-inoculated plants grown at 0 mol m−3 NaCl. In addition to these effects, leaf dry weight, area and chlorophyll content were also increased by Azospirillum inoculation when plants were grown at 40 mol m−3 NaCl. CONCLUSION: Azospirillum-inoculated lettuce seeds yield a higher number of transplanted plants with superior quality than non-inoculated controls grown at 0 or at 40 mol m−3 NaCl.